Water transport across the membrane of a direct toluene electro-hydrogenation electrolyzer: Experiments and modelling - Atienza Márquez, Antonio; Oi, Shota; Araki, Takuto; Mitsushima, Shigenori (Elsevier, 2024)
Toluene/methylcyclohexane is a promising liquid organic hydride for hydrogen storage and transport under ambient conditions. Direct toluene electro-hydrogenation electrolyzers, utilizing proton exchange membrane technology, offer benefits in reducing the reversible decomposition voltage and eliminating theoretical heat losses associated with conventional hydrogenation methods. Nevertheless, water transport across the membrane can inhibit the supply of toluene to reaction sites at the cathode. This study investigates water transport across the Nafion™ 117 membrane of an in-house electrolyzer cell, employing sulfuric acid and toluene solutions as the anode and cathode reactant, respectively, and operating at current densities from 0.1 to 0.8 A/cm2. The experiments show that the cathode toluene concentration has a negligible effect on drag water, while water flux increases with electric current and decreases with higher anode sulfuric acid concentrations. The modelling approach assumes electro-osmosis and diffusion mechanisms govern water transport. Simulations predict a linear decrease in the electro-osmotic drag coefficient from 2.3 to 1.6 as the sulfuric acid concentration rises from 0.1 to 1.5 mol/L, while the back diffusion flux increases linearly up to 2 mg/(min·cm2). These findings closely align with experimental data and previous literature, despite the high complexity of water transport in polymer electrolyte membranes.
Keywords: Electroósmosis; Tolueno; Hidrógeno; Water mass transport; Hydrogen energy technologies; Toluene/MCH organic hydride; Electrolyzer; Polymeric electrolyte membrane; Electro-osmosis